2007
DOI: 10.4314/tdj.v14i1.37566
|View full text |Cite
|
Sign up to set email alerts
|

Oral health knowledge, perceptions and behaviour among nursing students in a Nigerian tertiary hospital

Abstract: Aim: The purpose of the study was to investigate oral health knowledge, perceptions and behaviour amongst nursing students in a Nigerian tertiary hospital. Materials and methods: The study was conducted at University of Nigeria Teaching Hospital on 244 respondents aged 17 to 40 years, using self administered structured questionnaire. Result: Respondents showed high level of oral health knowledge. Most of them (68.3%), had never visited a dentist with females accounting for 144 (67.7%) (P > 0.05). About 58.0% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 13 publications
3
10
2
1
Order By: Relevance
“…[20] In this research, 94% of the participants chose morning as the appropriate time for cleaning their teeth, and similar result was also observed in Dhaka. [21] Graph 3: Prevalence of different types of cleaning tools among the study participants The prevalence of gingivitis among the study group in this research was 38% which was lower to research done by Taani et al where 28% Jordanian reported with bleeding from gums [22] also among the survey done in hospital in Nigeria where 28% gingival bleeding was recorded [23] and the results was contrary to the research done by Sarwar et al where the prevalence was 67%. [24] The results showed that the prevalence of oral hygiene maintained among the respondent was hundred percent, but gingival bleeding explains that it could be the consequences of inadequate brushing technique, frequency, timing, and usage of betel nut chewing which deteriorate the gingival conditions despite daily brushing.…”
Section: Discussioncontrasting
confidence: 56%
“…[20] In this research, 94% of the participants chose morning as the appropriate time for cleaning their teeth, and similar result was also observed in Dhaka. [21] Graph 3: Prevalence of different types of cleaning tools among the study participants The prevalence of gingivitis among the study group in this research was 38% which was lower to research done by Taani et al where 28% Jordanian reported with bleeding from gums [22] also among the survey done in hospital in Nigeria where 28% gingival bleeding was recorded [23] and the results was contrary to the research done by Sarwar et al where the prevalence was 67%. [24] The results showed that the prevalence of oral hygiene maintained among the respondent was hundred percent, but gingival bleeding explains that it could be the consequences of inadequate brushing technique, frequency, timing, and usage of betel nut chewing which deteriorate the gingival conditions despite daily brushing.…”
Section: Discussioncontrasting
confidence: 56%
“…In this study, the prevalence of gingival bleeding was 12.7% which is comparable to the findings reported among secondary school students in Ethiopia (17.4%),15 young army recruits in Israel (18.8%),5 and dental students in Saudi Arabia (19.2%) 16. However, it is lower than ≈25% and 28.8% reported among patients attending a tertiary Hospital in South-West7 and South-East regions of Nigeria10 respectively. It is also lower than 27.9% reported among adults in Kuwait 17.…”
Section: Discussionsupporting
confidence: 73%
“…A study showed that gingival bleeding was not perceived as an indicator of inflammatory disease thus hindering the propensity to seek professional care 9. In hospital-based studies in South-West7 and South-East regions of Nigeria,10 the prevalence of gingival bleeding were reported as ≈25% and 28.8% respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Good oral health is important for getting a good job, improving self-esteem, and succeeding in life [20]. Several factors may affect the oral health behavior of an individual, including the acquisition of Western education, culture, and values [6,21]. Oral health knowledge of schoolchildren is influenced by socioeconomic factors, such as gender, ethnicity, type of school, income as well as the educational level of their parents [9,22,23].…”
Section: Discussionmentioning
confidence: 99%